Innovation in the Processing of Native Round Fish: A Readjustment of the Processing Workflow for Salmonella spp. Control in a Fish Processing Plant in the State of Mato Grosso - Jaqueline Oliveira Reis; Nathaly Barros Nunes; Yuri Duarte Porto; Adelino Cunha Neto; Sara Rodrigues de Souza; Washington da Guia Fonseca; Alexsandro da Silva Siqueira; Luciana Kimie Savay-da-Silva; Eduardo Eustáquio de Souza Figueiredo (Animals)
Salmonella spp. is a pathogen detected in fish, although it is not part of its microbiota; the production and processing environment is the main source of contamination. Brazilian legislation recommends 5 ppm of free residual chlorine for fish washing, but Salmonella can still be present. The objective of this study was to evaluate flaws in the processing flowchart and propose adjustments to reduce Salmonella spp. on the fish surface. Ninety samples were analyzed in a fish processing plant in Mato Grosso, divided into three treatments: (1) conventional processing, (2) modified flowchart, and (3) modified flowchart adapted to the specific plant conditions. Treatment 2 completely eliminated Salmonella spp., while treatment 3 reduced contamination to 3.3%, compared to 56.7% in conventional processing. The success of the modified treatment was only possible due to the main changes implemented in the process, which included the separation of dirty areas (responsible for gill and scale removal) and clean areas (designated for the careful removal of viscera without rupture and for filleting). No statistical difference was found between treatments 2 and 3 (p = 1, CI 0.00000–39.00055), suggesting that the adjusted flowchart can be implemented on a large scale to ensure food safety (OR = ∞, CI = [7.655, ∞], p < 0.001). This study highlights the effectiveness of the adjusted flowchart in reducing Salmonella spp. contamination in fish, with treatment 2 resulting in a complete absence of contamination. Treatment 3 maintained low contamination levels, demonstrating practical applicability in meatpacking plants.